Potential of Plant Growth-Promoting Rhizobacteria (PGPR) from The Tobacco Rhizosphere in Prancak Village to Degrade Organic Matter - Hefdiyah, Hefdiyah; Ach. Kholish; Safitri, Soviana Fila (Biotropika: Journal of Tropical Biology, 2025)
Organic agriculture is growing in Sumenep due to heightened awareness of the negative impacts of synthetic chemical use. Utilising Plant Growth-Promoting Rhizobacteria (PGPR) from the rhizosphere of tobacco plants in Prancak Village presents an alternative to chemical fertilisers and pesticides. It may serve as a biostimulant, encouraging farmer independence and maintaining the organic farming practices. This study examined the diversity of bacteria in the rhizosphere of tobacco plants in Prancak Village. It also examined the efficiency of nitrogen-fixing and phosphate-solubilising bacteria, or PGPR, in decomposing organic matter. The bacterial population was measured using the total plate count method. The soil physicochemical factors considered included pH, texture, and colour, while the potential for organic matter degradation was assessed of measuring inhibition zones. The results showed that the PGPR population in the tobacco rhizosphere ranged from 0.83 to 6.68 × 106 CFU. Nine isolates of potential organic matter-degrading bacteria were identified, with index values for the Amylolytic Index (AI) ranging from 16.7 mm to 42.8 mm, Cellulolytic Index (CI) from 68 cm to 4.31 cm, Proteolytic Index (PI) from 2.05 mm to 5.94 mm, and Lipolytic Index (LI) from 1.62 mm to 5.20 mm.